SOME CONSIDERATIONS ON TURKESTAN AUTONOMY - Juraeva Zukhra (Web of Journals Publishing, 2025)
The article describes in detail the creation of the Turkestan autonomy, its composition and activities. It was also thought that the February Revolution of 1917 brought great changes to the life of Turkestan, that after the revolution many political organizations and parties advocating for independence and freedom were created in Turkestan, and that the progressive intelligentsia began to demand autonomy for Turkestan.
Keywords: Mukhtoriyat, Turkestan Mukhtoriyat, Kurultai, Provisional Council, Bolsheviks, Uzbek SSR, TASSR, progressive, Constituent Assembly.